2021
DOI: 10.1111/fwb.13851
|View full text |Cite
|
Sign up to set email alerts
|

Invasive forest pathogens affect the characteristics, microbial colonisation, and decomposition of leaf litter in streams

Abstract: Invasive tree pathogens threaten forests worldwide, but their effects on streams are poorly understood. Nevertheless, tree infections that lead to changes in the characteristics of litter inputs to streams may affect stream communities and ecosystem processes. We studied cross‐ecosystem effects derived from Phytophthora cinnamomi, Phytophthora ×alni, and Ophiostoma novo‐ulmi infection on Castanea sativa (chestnut), Alnus lusitanica (alder), and Ulmus minor (elm) trees, respectively, by assessing physical and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 106 publications
(151 reference statements)
2
9
1
Order By: Relevance
“…Nonetheless, apparent subtle changes in litter traits might result in major effects in consumer fitness (Pérez et al, 2021). Furthermore, this projected minor decrease in leaf quality adds to the decline of populations of this key species through Europe due to a disease caused by the pathogen Phytophthora alni (Bjelke et al, 2016), which also has been recently reported to alter the nutritional quality of leaf litter (Ferreira et al, 2021). Both factors are likely to trigger significant alterations to the functioning of forested streams (Alonso et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, apparent subtle changes in litter traits might result in major effects in consumer fitness (Pérez et al, 2021). Furthermore, this projected minor decrease in leaf quality adds to the decline of populations of this key species through Europe due to a disease caused by the pathogen Phytophthora alni (Bjelke et al, 2016), which also has been recently reported to alter the nutritional quality of leaf litter (Ferreira et al, 2021). Both factors are likely to trigger significant alterations to the functioning of forested streams (Alonso et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…At the southern limit of P . × alni distribution, occurring in Jerte river (Plasencia, Spain) [ 24 ] and Ceira river (Arouce, Portugal) [ 25 ], disease severity is lower than in the north. Tree infection is produced by zoospores in the roots or in the trunk during floods, leading to root rot, collar rot, small-size, sparse and often chlorotic foliage, crown dieback, and tree mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates reach almost 100%, with young trees usually dying in few months and old trees dying in years while losing vitality progressively [ 18 , 19 ]. Leaf litter of Alnus lusitanica Vít, Douda and Mandák infected trees has higher nutrient concentration than that from healthy trees due to reduced nutrient resorption before senescence, leading to fast decomposition of leaf litter [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations